THE INFLUENCE OF CORPORATE ENVIRONMENTAL PERFORMANCE ON ENVIRONMENTAL DISCLOSURE WITH ENVIRONMENTAL RISK AS A MODERATING VARIABLE - Rosiyana Dewi; Rulianto Situmorang (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
Currently environmental performance is information that can increase company value, encourage companies to always disclose it in various media, however, environmental risks also need to be considered. The objective of this study is to analyze the influence of environmental performance on environmental disclosure with environmental risk as a moderating variable. The population of this study are manufacture companies listed on the Indonesia Stock Exchange (IDX) in 2016-2018. The sampling technique used is purposive sampling method, so there are 75 sample obtained that meet the criteria. The analytical method used to test the hypotheses in this study is multiple regression analysis. The results show that environmental performance and environmental risk have a significant positive influence on environmental disclosure, while environmental risk significantly weaken the influence of environmental performance on environmental disclosure.